Sentiment Analysis of Twitter Social Media to Online Transportation in Indonesia Using Naïve Bayes Classifier - Dini Fakta Sari; Deborah Kurniawati; Edy Prayitno; Irfangi Irfangi (Journal of International Conference Proceedings (JICP), 2019)
The application of information technology in transportation services is a positive development felt by the community with the emergence of various online transportation services. On the other hand, nowadays society cannot escape the use of social media in communicating and interacting with other parties. This research was conducted to determine the relationship between the use of social media and the use of online transportation services. The study was conducted using the Naïve Bayes Classifier method to analyze Twitter social media sentiment towards online transportation in Indonesia. The study was conducted by processing 1009 data, consisting of 900 training data and 109 test data. From the results of testing of 109 training data obtained 11% had a positive value, 14% negative value, and the rest, which is 75% neutral value. While the test accuracy test for 109 data resulted in an accuracy of 84%. The results of the study show that most of the use of Twitter social media in Indonesia does not affect the user's decision to utilize online transportation services.